Factors that affect the participation of students towards recycling activity: case study at UiTM Kedah / Nurhazirah Mohd Tharimazi and Juhaiza Jusoh - Mohd Tharimazi, Nurhazirah; Jusoh, Juhaiza (2012)
This papers aims to identify factors that lead to participation in recycling activity among UiTM Kedah student. The respondent in this research are involve students to know which factors lead them to get involved in recycling activity. Recyling has been adopted as way to reduce waste and ease the use of landfills and incenerators, with most currently deals with limited ground sites and raised pollutions concern all together. However, recycling activity could not be performed without public participation and this result will leading to many problems such as health issues and pollution. Two variables have been identified to answer the research question, namely knowledge and facilities provided in relation to public participation among UiTM Kedah student. Sample of 285 respondents has been extracted from the population using stratified random sampling.